On the Role of Abrupt Solar Wind Pressure Changes in Forbidden Energetic Electron Enhancements - Alla V. Suvorova; Alexei V. Dmitriev (Universe)
The sudden increase of fluxes of quasi-trapped energetic electrons under the Earth’s radiation belt (ERB) has remained a puzzling phenomenon for decades. It is known as enhancements of forbidden energetic electrons (FEEs). The FEE enhancements are occasionally observed by low-Earth orbit NOAA/POES satellites. Previously, no strong correlation was established between FEEs and geomagnetic activity, while external control of FEE occurrence by solar activity and interplanetary parameters was revealed on a long time-scale. Two important questions are still open: (1) key parameters of the mechanism and (2) solar wind drivers or triggers. In the present study we conducted detailed analysis of three FEE events that occurred during the greatest geomagnetic storms, which dramatically affected space weather. The FEE enhancements occurred under northward IMF and, thus, Bz and convection electric fields could have been neither driver nor trigger. We found that an abrupt and significant change in solar wind pressure is a key solar wind driver of the FEE enhancements observed. The characteristic time of FEE injection from the inner edge of the ERB at L-shell 1.2 to the forbidden zone at L < 1.1 was estimated to be 10–20 min. In the mechanism of ExB drift, this characteristic time corresponds to the radial inward transport of electrons caused by a transient electric field with the magnitude ~10 mV/m.